2022
DOI: 10.1093/ije/dyac212
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the role of non-alcoholic fatty liver disease in cardiovascular diseases and type 2 diabetes: a Mendelian randomization study in Europeans and East Asians

Abstract: Background Whether non-alcoholic fatty liver disease (NAFLD) causes cardiovascular disease (CVD) and type 2 diabetes (T2D) is unclear and possible differences between ethnicities have not been thoroughly explored. We used Mendelian randomization (MR) to assess the role of NAFLD in CVD and T2D risk in Europeans and East Asians. Methods We conducted a MR study using genetic predictors of alanine aminotransferase (ALT), liabilit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 54 publications
3
9
0
Order By: Relevance
“…40 These MR studies suggested that NAFLD and cirrhosis were risk factors for the diseases/disorders of interest. [30][31][32][33][34][35][36][37][38][39][40] Consistent results were observed in prior observational studies. 41,42 These results implied that NAFLD and cirrhosis may interact with some other factors and then increase liver cancer risk.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…40 These MR studies suggested that NAFLD and cirrhosis were risk factors for the diseases/disorders of interest. [30][31][32][33][34][35][36][37][38][39][40] Consistent results were observed in prior observational studies. 41,42 These results implied that NAFLD and cirrhosis may interact with some other factors and then increase liver cancer risk.…”
Section: Discussionsupporting
confidence: 90%
“…A MR study investigated the potential causal relationship between primary biliary cirrhosis and hypothyroidism 40 . These MR studies suggested that NAFLD and cirrhosis were risk factors for the diseases/disorders of interest 30–40 . Consistent results were observed in prior observational studies 41,42 .…”
Section: Discussionsupporting
confidence: 53%
See 1 more Smart Citation
“…In conclusion, our findings add to the growing body of literature describing the complexity and diversity of the genetic underpinnings of cardiovascular traits across different populations 8183 . This work lays a foundation for more precise and personalized approaches to preventing and managing cardiovascular diseases, ultimately aiming to reduce health disparities across different ethnic groups.…”
Section: Discussionsupporting
confidence: 64%
“…In the literature we reviewed, we found no MR analysis results about a causal association between GGT level and stroke. We did find studies that used MR analyses to link stroke with another indication of liver function, such as non-alcoholic fatty liver disease or bilirubin level [6,23,[60][61][62]; in those studies non-alcoholic fatty liver disease had a limited effect on stroke and showed controversial results. Although we used two-sample MR as a research method to reduce bias, we deemed alcohol to be a confounding factor because it has a substantial effect on GGT level.…”
Section: Discussionmentioning
confidence: 99%